Regulation of sinus node pacemaking and atrioventricular node conduction by HCN channels in health and disease. (November 2021) - Boyett, Mark R.; Yanni, Joseph; Tellez, James; Bucchi, Annalisa; Mesirca, Pietro; Cai, Xue; Logantha, Sunil Jit R.J.; Wilson, Claire; Anderson, Cali; Ariyaratnam, Jonathan; Stuart, Luke; Nakao, Shu; et al.
Abstract: The funny current, I f, was first recorded in the heart 40 or more years ago by Dario DiFrancesco and others. Since then, we have learnt that I f plays an important role in pacemaking in the sinus node, the innate pacemaker of the heart, and more recently evidence has accumulated to show that I f may play an important role in action potential conduction through the atrioventricular (AV) node. Evidence has also accumulated to show that regulation of the transcription and translation of the underlying Hcn genes plays an important role in the regulation of sinus node pacemaking and AV node conduction under normal physiological conditions - in athletes, during the circadian rhythm, in pregnancy, and during postnatal development - as well as pathological states - ageing, heart failure, pulmonary hypertension, diabetes and atrial fibrillation. There may be yet more pathological conditions involving changes in the expression of the Hcn genes. Here, we review the role of I f and the underlying HCN channels in physiological and pathological changes of the sinus and AV nodes and we begin to explore the signalling pathways (microRNAs, transcription factors, GIRK4, the autonomic nervous system and inflammation) involved in this regulation. This review is dedicated to Dario DiFrancesco on his retirement.